PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK MOTATO - Anthony Tanaya; Sri Nathasya Br Sitepu (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2022)
The Sale of mashed potato products from Motato are still not on target. Increasing sale becomes priority for Mototo by doing improvement on marketing activities especially in product quality, price, and promotion. This research is done to find out the effect of product quality, price, and promotion on purchase decision of Motato product. This research uses quantitative approach with population of 70 respondents with sampling technique that is a saturated sample. This search is also use multiple linear regression analysis method that is processed through SPSS. The method of data collection is done by distributing online questionnaires through Google form. The results of the research show that product quality, price, and promotion have significant effect on purchase decision with significant value of 0,009 t test result of product quality variable, 0,010 price dan 0,000 promotion. All significant values are at the number < 0,05. Therefore, it can be concluded that product quality, price, and promotion variable after significant on purchase decision of Motato product